2020
DOI: 10.1093/gigascience/giaa075
|View full text |Cite
|
Sign up to set email alerts
|

A generalizable data-driven multicellular model of pancreatic ductal adenocarcinoma

Abstract: Background Mechanistic models, when combined with pertinent data, can improve our knowledge regarding important molecular and cellular mechanisms found in cancer. These models make the prediction of tissue-level response to drug treatment possible, which can lead to new therapies and improved patient outcomes. Here we present a data-driven multiscale modeling framework to study molecular interactions between cancer, stromal, and immune cells found in the tumor microenvironment. We also develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 80 publications
0
33
0
Order By: Relevance
“…Next, we identified and investigated the inflammation-associated hypomethylation-high expression genes and hypermethylation-low expression genes and their potential upstream regulatory mechanisms in PDAC, respectively. Functional enrichment analysis showed that these hypomethylation-high expression genes were involved in blood vessel morphogenesis, cytokine-mediated signaling pathway, regulation of cell adhesion, and pathways in cancer, which are well known in regulating the progression of PDAC [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Next, we identified and investigated the inflammation-associated hypomethylation-high expression genes and hypermethylation-low expression genes and their potential upstream regulatory mechanisms in PDAC, respectively. Functional enrichment analysis showed that these hypomethylation-high expression genes were involved in blood vessel morphogenesis, cytokine-mediated signaling pathway, regulation of cell adhesion, and pathways in cancer, which are well known in regulating the progression of PDAC [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To integrate newly discovered pathways, appropriate computational models are required to describe cell-to-cell interactions and protein expression dynamics. The conventional computational models include, but not limited to, mechanistic models [ 69 - 71 ], statistical models [ 72 , 73 ], and data-driven models [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the ESM concentration should be θ times the basal in order to be registered. Incorporating basal secretion in this way allows for a more general model of signaling dynamics better able to capture the leaky nature of real systems (61, 62). Another key parameter of the ESM communication mechanism is the effective interaction distance λ , which is derived from the molecule concentration decay rate and the diffusion coefficient: .…”
Section: Model Descriptionmentioning
confidence: 99%